Injection rate estimation to numerically assess CO2 sequestration in depleted gas reservoirs. Issue 13 (2nd July 2020) - Raza, Arshad; Gholami, Raoof; Rabiei, Minou; Rasouli, Vamegh; Rezaee, Reza
ABSTRACT: Depleted gas reservoirs are known as geological media for the sequestration of carbon dioxide (CO2 ). A large amount of studies attempting to estimate the injection rate of CO2 by analytical and numerical modeling but selection of a suitable injection rate based on the effect of the remaining gas has not been fully understood for in depleted gas fields. This study attempts to present a scheme to estimate the injection rate for CO2 sequestration in depleted gas reservoirs which can help to avoid the lengthy simulation time often required. An analytical method was suggested to estimate the favorable steady-state injection rate for three-phase system (CO2 -gas-brine). For the sequestration, CO2 was injected at the estimated and overestimated injection rate to evaluate their impacts on the storage injectivity and capacity. The results obtained indicated that the injection rate estimation approach proposed can be a great asset to evaluate the injectivity and the sequestration potential of the depleted gas reservoirs.